Republicanism and liberalism in America and the German states, 1750-1850 - Henretta, James A.; Heideking, Jürgen, 1947-2000 (Publications of the German Historical Institute., 2002)
Represents the cooperative effort of American and German scholars to systematically study the similarities and differences in the understanding of republicanism and liberalism in America and the German states. The book stimulates new efforts toward a comprehensive interpretation of political, intellectual, and social developments in the 'modernizing' Atlantic world.